Early cholangioscopy-assisted electrohydraulic lithotripsy in difficult biliary stones is cost-effective. (July 2021) - Alrajhi, Saad; Barkun, Alan; Adam, Viviane; Callichurn, Kashi; Martel, Myriam; Brewer, Olaya; Khashab, Mouen A.; Forbes, Nauzer; Almadi, Majid A.; Chen, Yen-I
Background and Aims: Single-operator cholangioscopy-assisted electrohydraulic lithotripsy (SOC-EHL) is effective and safe in difficult choledocholithiasis. The optimal timing of SOC-EHL use, however, in refractory stones has not been elucidated. The following aims to determine the most cost-effective timing of SOC-EHL introduction in the management of choledocholithiasis. Methods: A cost-effectiveness model was developed assessing three strategies with a progressively delayed introduction of SOC-EHL. Probability estimates of patient pathways were obtained from a systematic review. The unit of effectiveness is complete ductal clearance without need for surgery. Cost is expressed in 2018 US dollars and stem from outpatient US databases. Results: The three strategies achieved comparable ductal clearance rates ranging from 97.3% to 99.7%. The least expensive strategy is to perform SOC-EHL during the first endoscopic retrograde cholangiography pancreatography (ERCP) (SOC-1: 18, 506$). The strategy of postponing the use of SOC-EHL to the third ERCP (SOC-3) is more expensive (US$18, 895) but is 2% more effective. (0.9967). SOC-EHL during the second ERCP in the model (SOC-2) is the least cost-effective. Sensitivity analyses show altered conclusions according to the cost of SOC-EHL, effectiveness of conventional ERCP, and altered willingness-to-pay (WTP) thresholds with early SOC-1 being the most optimal approach below a WTP cut-off of US$20, 295. Conclusions: Early utilization of SOC-EHL (SOC-1) in difficult choledocholithiasis may be the least costly strategy with an effectiveness approximating those achieved with a delayed approach where one or more conventional ERCP(s) are reattempted prior to SOC-EHL introduction.